The Impact of Digital Technology and Information Communication Technology on English Language in Nigeria (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The proliferation of digital technology and Information Communication Technology (ICT) has significantly influenced the use and teaching of the English language in Nigeria. This transformation is evident in various spheres including education, media, and everyday communication. In educational settings, digital tools and ICT have revolutionized English language instruction, providing innovative platforms for interactive learning, access to a vast array of online resources, and the integration of multimedia content that enhances comprehension and engagement. Furthermore, social media and digital communication platforms have altered the dynamics of language use, introducing new forms of expression, slang, and abbreviations that reflect a hybrid linguistic culture. While these technologies have democratized access to information and fostered global communication, they have also presented challenges such as the erosion of formal writing skills and the potential for the proliferation of non-standard English. Additionally, the digital divide remains a critical issue, as unequal access to technology exacerbates educational and linguistic disparities. This study adopts a qualitative research methodology, utilizing a comprehensive literature review and thematic analysis to explore these phenomena. The theoretical framework is grounded in the Theory of Blended Learning Instructional Approach (BLIA), which provides insights into the integration of traditional and digital learning methods. This abstract encapsulates the dual-edged impact of digital technology and ICT on English in Nigeria, highlighting both the advancements in linguistic proficiency and the emerging challenges that need to be addressed to ensure equitable and effective language education in the digital age.
Keywords: Digital; Information; Communication; Technology; Language